2009
DOI: 10.1002/art.24702
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet radiation intensity predicts the relative distribution of dermatomyositis and anti–Mi‐2 autoantibodies in women

Abstract: Objective-Because studies suggest that ultraviolet radiation (UVR) modulates myositis phenotype and Mi-2 autoantigen expression, we conducted a retrospective investigation to determine if UVR may influence the relative prevalence of dermatomyositis and anti-Mi-2 autoantibodies in the United States.Methods-We assessed the relationship between surface UVR intensity in the state of residence at the time of onset with the relative prevalence of dermatomyositis and myositis autoantibodies in 380 myositis patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 16 publications
10
80
0
3
Order By: Relevance
“…The differential association of Sjögren syndrome between male and female patients with dermatomyositis may be explained by the different pathogenesis of dermatomyositis in the different sexes. Past studies of dermatomyositis showed sex differences in risk factors 22 and autoantibody profiles. 24 Furthermore, genetic studies of pediatric dermatomyositis showed sexual dimorphism in the gene-gene interaction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The differential association of Sjögren syndrome between male and female patients with dermatomyositis may be explained by the different pathogenesis of dermatomyositis in the different sexes. Past studies of dermatomyositis showed sex differences in risk factors 22 and autoantibody profiles. 24 Furthermore, genetic studies of pediatric dermatomyositis showed sexual dimorphism in the gene-gene interaction.…”
Section: Discussionmentioning
confidence: 97%
“…20,21 It is important to gain a more accurate understanding of this increased risk of Sjögren syndrome in dermatomyositis. Although research into dermatomyositis showed sex differences in risk factors, 22 cytokine expression, 23 autoantibodies profile 24 and certain dermatomyositis-related outcomes, 2 it is unknown whether the association with Sjögren syndrome differs among men and women with dermatomyositis.…”
mentioning
confidence: 99%
“…Pacjenci z tym rodzajem przeciwciał mają typowe dla DM zmiany skórne, takie jak objaw i/lub grudki Gottrona, rumień heliotropowy, rumień i rozrost obrąbka naskórkowe-go paznokcia, zmiany rumieniowe dotyczące podstawy karku, dekoltu, górnej części pleców i ramion (rumień w kształcie litery V i objaw szala). Występo-wanie przeciwciał anty-Mi-2 wiąże się ze szczególnie nasiloną fotowrażliwością, a u kobiet ich miano dodatnio koreluje z pochłoniętą dawką promieniowania ultrafioletowego [1,20]. Pacjenci, u których stwierdza się przeciwciała anty-Mi-2, mają mniej nasilone objawy mięśniowe, znacznie rzadziej zajęcie płuc oraz zapalenie stawów i zazwyczaj dobrze odpowiadają na leczenie glikokortykosteroidami (GKS).…”
Section: Przeciwciała Anty-mi-2unclassified
“…There are number of conflicting hypotheses which indicate that differences in the amount of adipose tissue in males and females and in their skins may lead to the variation in vitamin D synthesis. Number of studies has demonstrated decreased bioavailability of fat soluble vitamin D3 from cutaneous and dietary sources because of its deposition in body fat [24][25][26][27]. This may point toward decreased vitamin D levels in women because of their excessive adiposity as compared to men.…”
Section: Is Vitamin D Synthesis Gender Specific?mentioning
confidence: 99%
“…Individuals who have the GSTM1 null genotype and are missing the enzyme may, therefore, be at an increased risk of DNA damage and can induce the onset of lupus [122]. Work done by Love et al to study the distribution of myositis phenotypes and ultraviolet radiation exposure in the United States showed that ultraviolet radiation may modulate the clinical and immunological expression of autoimmune disease in women [123]. The above evidence points toward the stimulation and exacerbation of autoimmune process in specific disease, whereas, on the other hand, ultraviolet radiations can also prevent or reduce the symptoms of other autoimmune diseases by vitamin D formation in skin as elaborated in various parts of this chapter.…”
Section: Role Of Sunlight In Autoimmune Diseasesmentioning
confidence: 99%